HOLOCENE MONSOONAL DYNAMICS AND FLUVIAL TERRACE FORMATION IN THE NORTHWEST HIMALAYA, INDIA - Bookhagen B.; Strecker M.R.; Thiede R.C.; Fleitmann D.; Nishiizumi K. (My University, 2006)
Aluminum-26 and beryllium-10 surface exposure dating on cut-and-fill river-terrace surfaces from the lower Sutlej Valley (northwest Himalaya) documents the close link between Indian Summer Monsoon (ISM) oscillations and intervals of enhanced fluvial incision. During the early Holocene ISM optimum, precipitation was enhanced and reached far into the internal parts of the orogen. The amplified sediment flux from these usually dry but glaciated areas caused alluviation of downstream valleys up to 120 m above present grade at ca. 9.9 k.y. B.P. Terrace formation (i.e., incision) in the coarse deposits occurred during century-long weak ISM phases that resulted in reduced moisture availability and most likely in lower sediment flux. Here, we suggest that the lower sediment flux during weak ISM phases allowed rivers to incise episodically into the alluvial fill. © 2006 Geological Society of America.
Keywords: FLUVIAL PROCESSES; GEOMORPHOLOGY; HIMALAYA; MONSOON; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен